Sniper Action in Sarajevo during the Siege Period 1992-1995. - Zilha Mastalić Košuta (Historijski pogledi, 2023)
The area of Sarajevo at the beginning of April 1992 was violently divided. Units of the 4th Corps of the 2nd Military District of the Yugoslav People's Army (JNA), the armed forces that were gathered and supported the Serbian Democratic Party (SDS) as well as many local and foreign volunteers and mercenaries occupied strategic positions in and around Sarajevo. Open armed aggression began after Bosnia and Herzegovina was recognized as an international independent state. After that, Sarajevo was blocked and put under siege for almost four years. After the partial withdrawal of the JNA from Bosnia and Herzegovina, the 2nd Military District of the JNA was transformed into a part of the Army of the Serbian Republic of Bosnia and Herzegovina (VSr RBiH), from August 1992 under the name of the Army of the Republika Srpska (VRS). Through the transformation, the 4th Corps of the JNA became the Sarajevo-Romanian Corps (SRK) VSr RBiH. In the period of the four-year siege of Sarajevo, in order to control Sarajevo, the said forces carried out a “coordinated systematic and long-term campaign of shelling and sniping” in order to “kill, maim, injure and terrorize the civilian population of Sarajevo”. In addition to artillery attacks, which were the most widespread way in which the inhabitants of Sarajevo were killed, another frequent way of killing was sniper attacks. The sniper clearly sees his victim and kills him with intent. Residents of Sarajevo were intentional victims of sniper attacks and were not safe anywhere. Without water, electricity, gas and other necessities of life, the residents fought a daily struggle for bare survival. It was a day and night fight for survival. Cruel individual and mass murders of civilians, including those of the youngest residents, followed by daily wounding, terrorizing, violations of psychological integrity, illegal actions and others, are part of the crimes committed against the inhabitants of Sarajevo in the period 1992-1995. years. Guided primarily by the verdicts and documents of the International Tribunal for War Crimes in The Hague, as well as other relevant archival documents and the statements and expertise of experts, the author shows in her work what the sniping campaign meant. A very important part is the display and description of the types of weapons that were used in such operations, as well as the description of localities and parts of the city from which snipers were most often used. Based on these data, it is very clear to see what the daily life of the inhabitants of the city under siege looked like. The organization of sniper training as well as the places where the training was conducted and in what way are also important parts of the work. The demand and delivery of sniper weapons and ammunition to the Sarajevo-Romania Corps, as well as the identities of the snipers, as well as hired mercenaries and volunteers from other countries, are parts of the work presented by the author. Based on the examples of the victims of sniping, primarily the killing of children, it is clear that the enemy's goal was to kill civilians with intent, directly and in a targeted manner. In this section, the investigated and identified minor victims of sniper attacks as well as the circumstances of the murder are presented in chronological order. As a clear indication that the sniper's intention was to kill them or seriously injure them with permanent consequences, the parts of the body that were hit, which are very often the head, the area around the heart, the stomach, and the lungs, are also shown. In the final part of the paper, the emphasis is on the prosecution and non-prosecution of persons responsible for crimes committed by snipers, before domestic and international courts. Although there is irrefutable evidence of sniper killings of Sarajevo residents, very few or no indictments are filed against those responsible. The direct perpetrators - snipers, who killed the inhabitants of Sarajevo with intent, have not yet been brought to justice and convicted of the crime.